IMPLEMENTASI KURIKULUM MERDEKA DALAM PENINGKATAN PENDIDIKAN KARAKTER PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Defa, Defa; Lasmawan, I Wayan; Kertih, I Wayan (Universitas Negeri Medan, 2023)
IPS education is one of the subjects in elementary school. The purpose of social studies learning in elementary schools is to see the perspective of students' social life in socializing with other human beings in dealing with and solving problems faced by students everyday. In the Merdeka Curriculum, students are prepared not only with knowledge skills, but also with the character of students in living their daily lives as good Indonesian citizens. For this reason, with social studies learning in elementary schools, it becomes the basis for students to learn about social life and social participation in society. Of course, at school, the role of the independent curriculum in social studies learning is very important in building the character of students in elementary schools according to the profile of Pancasila students.